Macroeconomic risks after a decade of microeconomic turbulence: South Africa 2007-2020 - Ricardo Hausmann; Federico Sturzenegger; Patricio Goldstein; Frank Muci; Douglas Barrios (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This study analyses the performance of macroeconomic policy in South Africa in 2007- 2020 and outlines challenges for policy in the coming decade. After remarkable economic growth in 1997-07, South Africa's progress slowed dramatically in 2009 with the global financial crisis. Real GDP growth decelerated more than in other emerging markets and mineral exporting peers and never recovered pre-crisis levels. In addition, the budget deficit that provided counter-cyclical support to the economy was never reigned in, leading to a rapidly rising public debt load. The study assesses three accounts of South Africa's post-GFC growth and fiscal slump: (1) an external story; (2) a macro story; and (3) a microeconomic story. Evidence of strong linkages between micro- and political developments and growth performance is provided.
Keywords: E63; E65; O55; 330; macroeconomic policy; economic growth; emerging markets; South Africa